Proangiogenic Growth Factors Potentiate In Situ Angiogenesis and Enhance Antifungal Drug Activity in Murine Invasive Aspergillosis - Ben-Ami, Ronen (Oxford University Press, 2013)
In invasive pulmonary aspergillosis, direct invasion and occlusion of pulmonary vasculature by Aspergillus hyphae causes tissue hypoxia, which is enhanced by secreted fungal metabolites that downregulate compensatory angiogenic signaling pathways. We assessed the effects of basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) on survival rates, fungal burden, and in situ angiogenesis in a murine invasive pulmonary aspergillosis model. bFGF and VEGF monotherapy significantly increased survival rates and potentiated the activity of amphotericin B. bFGF-containing regimens were associated with reduced tissue fungal burdens. bFGF and VEGF reversed the antiangiogenic activity of Aspergillus fumigatus; however, VEGF induced the formation of immature neovessels, providing an explanation for its lesser efficacy. Treatment with bFGF plus amphotericin B was associated with neutrophil influx into Aspergillus-infected pulmonary tissue, suggesting that this combination limits fungal growth through neutrophil trafficking. Vasculogenic pathways are unexplored targets for the treatment of invasive pulmonary aspergillosis and may potentiate both innate immunity and antifungal drug activity against A. fumigatus.